Markskadefri avverkning - från traktplanering till plantering - Södergren, Oscar (2014)
This study is made for Södra skog and is concerning how to minimize soil damage from planning to plantation. The purpose of the study is from the respondent’s perspectives; their own ideas and approaches. What emerged from the interviews is that the communication between the different organization levels can be improved. It is also important to prevent damage on the soil and to have in mind that the process of planning tracks to plantation continues for a long time and because of that, the soil condition meanwhile will change.